KERAGAMAN FORAMINIFERA BENTONIK KECIL RESEN PADA CORE-01 DI PERAIRAN JEPARA, PROVINSI JAWA TENGAH - Aswad, Siti Mulia Nurul; Jurnaliah, Lia; -, winantris (Bulletin of Scientific Contribution, 2014)
Foraminifera live from shallow marine into deep marine. Environment itself has their own characteristic of foraminifera. Indonesia which is an archipelago country has highly foraminifer’s diversity. Research area is located in Jepara Water and is a part of Java Sea. Geographically, core-01 is lied on 05055’18.66” Latitudes and 110042’34.55” Longitudes. This research is done in order to know the diversity of recent small benthic foraminifera , so that, is there an environmental changes of core-01. Quantitative method is used on 12 sample sediment below sea floor with interval depth 50.00 – 50.55 meter. The identified recent small benthonic foraminifera are compound of 43 genera and 73 species. Based on research, there are changes of diversity genera, diversity species, and individual numbers of recent small benthic foraminifera. Those changes can be used as an indicator of vertically core-01 environmental changes.